PENERAPAN APLIKASI ARCGIS PADA KONTUR DAERAH ALIRAN SUNGAI SILAU DALAM PENGGUNAAN LAHAN DI KOTA KISARAN - Kiki Kurnia Roseka; Muhammad Irwansyah; Intan Zahar (Universitas Asahan, 2025)
Silau River is a river that flows for 13.3 kilometers across Kisaran City, Asahan Regency. The rapid development of Kisaran City as the district capital has caused many land conversions around the Silau River Watershed. The large number of land conversions causes environmental damage to rivers. This research aims to determine the development of width, depth and scour that occurs around the river basin. Applying contour maps to river basins will reveal the area of ​​buildings and plantations that are being converted into land use. Contour maps can be built in the ArcGis application version 10.3. With the ArcGis 10.3 application, you will get the area that is being converted into land. The treatment carried out is controlling and normalizing areas that have changed function and replanting protected plants around river banks